Islamisation of engineering education in International Islamic University Malaysia (IIUM): problems and prospect - Ahmad, Zuraida; Ismail, Ahmad Faris; Shafie, Amir Akramin; Ihsan, Sany Izan; Halim, Zahurin; Mohamad, Souad A. (Research Management Centre, International Islamic University Malaysia, 2011)
The surge for infusing of Islamic knowledge and values into engineering education emerge having realized the gross inadequacies of the western/secular engineering education, which aimed only at outward development of individuals. The intention of integrating the Islamic values is to develop a balanced student personality, pleasing to God and to fellow humans, who promote and encourage ma’ruf (good) and fight munkar (evil). This paper is an attempt to examine the existing engineering education system in Kulliyyah of engineering, IIUM. It examines two fields, which are germane to the whole discussions on the subject matter. The two concepts are the existing engineering education and the Islamic knowledge that is and will be integrated in the engineering curriculum. The authors are also proposing frameworks for the Islamisation of engineering programme, highlighting some obstacles in the proposed frameworks as well as likely trying to encounter and suggest solutions for its success.